2010
DOI: 10.1111/j.1743-6109.2010.01888.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Oral Mirodenafil in the Treatment of Erectile Dysfunction in Diabetic Men in Korea: A Multicenter, Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Introduction Mirodenafil is a newly developed selective phosphodiesterase type 5 (PDE5) inhibitor for the treatment of erectile dysfunction (ED). Aim To evaluate the efficacy, safety and tolerability of mirodenafil in the treatment of ED in Korean men with diabetes. Methods A multicenter, randomized, double-blind, placebo-controlled, parallel-group, fixed-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 39 publications
(47 reference statements)
4
45
1
1
Order By: Relevance
“…The optimal doses in terms of efficacy and safety were determined from these studies to be 50 and 100 mg. Mirodenafil was shown to be effective and safe in men with ED concomitantly taking antihypertensive medications (Paick et al, 2010). In 112 Korean men with ED and diabetes, Park et al (2010a) showed in an RCT that mirodenafil was effective and well tolerated. The most common adverse events were facial flushing, headache, nausea, and eye redness.…”
Section: Drugs For Nonintracavernosal Administrationmentioning
confidence: 99%
“…The optimal doses in terms of efficacy and safety were determined from these studies to be 50 and 100 mg. Mirodenafil was shown to be effective and safe in men with ED concomitantly taking antihypertensive medications (Paick et al, 2010). In 112 Korean men with ED and diabetes, Park et al (2010a) showed in an RCT that mirodenafil was effective and well tolerated. The most common adverse events were facial flushing, headache, nausea, and eye redness.…”
Section: Drugs For Nonintracavernosal Administrationmentioning
confidence: 99%
“…The clinical efficacy and tolerability of mirodenafil in patients with ED of various underlying etiologies and severities have been assessed in several randomized, placebo-controlled clinical studies [Paick et al 2008a[Paick et al , 2008b[Paick et al , 2010Park et al 2010;Chung et al 2013]. Tables 2 and 3 of the Sexual Encounter Profile (SEP3)] in the mirodenafil treatment groups (44.9-63.2%) were significantly greater than 18.6% in the placebo group.…”
Section: Metabolismmentioning
confidence: 99%
“…However, further head-tohead comparative studies between the PDE5Is are needed because it is difficult to directly compare the efficacy between different PDE5Is due to differences in baseline characteristics of patients, inclusion criteria, outcome measures, dosing schedules and treatment periods. Furthermore, four of the five randomized clinical trials of mirodenafil excluded the nonresponders to PDE5Is [Paick et al 2008a[Paick et al , 2008b[Paick et al , 2010Park et al 2010], while only a few sildenafil trials, half of vardenafil trials and only a third of tadalafil trials excluded men with ED that did not respond to previous PDE5Is [Tsertsvadze et al 2009]. Thus, the difference could limit the comparison of treatment outcomes of mirodenafil trials with those of historical trials of vardenafil, tadalafil or sildenafil.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analysis identified three randomized controlled trials (RCTs) [2][3][4] including 374 participants and concluded that mirodenafil is effective and well-tolerated therapy for ED. However, the main issue needed to be addressed is that whether it is reasonable to simply integrate data from the three RCTs.…”
mentioning
confidence: 99%